The Influence of Madrasah Culture on Student Discipline at an Islamic Junior High School in Makassar - Sulaiman, Umar; Hamsiah Djafar,; Mihrani,; Chaerul Mundzir, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Madrasah culture encompasses the values, beliefs, attitudes, and behaviors that are regularly patterned and reflect habits aimed at adapting to the environment, as well as the madrasah's perspective on problem-solving. These cultural elements are shaped through the institution's history and experience. This paper presents the findings of research that investigates the extent to which madrasah culture influences student discipline. The study employs an ex post facto design with a quantitative approach. The research sample consisted of students from a madrasah in Makassar City, selected through simple random sampling. Data were collected via questionnaires and analyzed using both descriptive and inferential statistics. The results indicate a significant influence of madrasah culture on student discipline. These findings underscore the importance of strengthening student discipline through the cultivation of madrasah culture, particularly within the context of the studied institution. Abstrak: Budaya madrasah mencakup nilai-nilai, keyakinan, sikap, dan perilaku yang terpolakan secara rutin, mencerminkan kebiasaan untuk beradaptasi dengan lingkungan, serta perspektif madrasah dalam memecahkan masalah. Elemen-elemen budaya ini terbentuk melalui sejarah dan pengalaman institusi tersebut. Artikel ini menyajikan hasil penelitian yang bertujuan untuk mengkaji sejauh mana budaya madrasah memengaruhi disiplin siswa. Penelitian ini menggunakan desain ex post facto dengan pendekatan kuantitatif. Sampel penelitian terdiri dari siswa di sebuah madrasah di Kota Makassar, yang dipilih melalui teknik pengambilan sampel acak sederhana. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan adanya pengaruh budaya madrasah terhadap disiplin siswa. Temuan ini menekankan pentingnya memperkuat disiplin siswa melalui budaya madrasah yang telah dibangun, khususnya dalam konteks institusi yang diteliti.